AKTIVITAS ANTIJAMUR PELAPUK KAYU NANOPARTIKEL KITOSAN-EKSTRAK N-HEKSAN DAGING BUAH KAYU GADIS (Cinnamomum parthenoxylon) - Ekasari, Munifilia; Nurhasana, Devi; Mudyanto, Andre; Avidlyandi, Avidlyandi; Banon, Charles; Adfa, Morina (LP4MK STKIP PGRI Lubuklinggau, 2023)
This study aims to synthesize chitosan nanoparticles - n-hexane extract of Cinnamomum parthenoxylon (CP) fruit using the ionic gelation method, to characterize them, and to determine their antifungal activity against the wood-rotting fungi Trametes versicolor and Fomitopsis palustris. Chitosan-CP extract nanoparticles were formulated with chitosan:Na-TPP:CP extract ratio of 1:1:0.5. Particle size and polydispersity index were determined using a particle size analyzer (PSA), and particles morphology was observed using a scanning electron microscope (SEM), and antifungal activity was measured using agar media. The results revealed that the average size of chitosan nanoparticles (base) was 276.9 nm, while the average size of chitosan-CP extract nanoparticles was 807.6 nm. The polydispersity index (PI) of both nanoparticles was greater than 0.7. Observations of the nanoparticles' morphology revealed that aggregation/agglomeration formed in the resulting particles. Both nanoparticles chitosan (base) and chitosan-CP extract inhibited the growth of white rot fungi (T. versicolor) more than brown rot fungi (F. palustris), as measured by the inhibitory zone.